2022
DOI: 10.3389/fimmu.2022.852419
|View full text |Cite
|
Sign up to set email alerts
|

The Role of microRNA in the Inflammatory Response of Wound Healing

Abstract: Wound healing, a highly complex pathophysiological response to injury, includes four overlapping phases of hemostasis, inflammation, proliferation, and remodeling. Initiation and resolution of the inflammatory response are the primary requirements for wound healing, and are also key events that determines wound quality and healing time. Currently, the number of patients with persistent chronic wounds has generally increased, which imposes health and economic burden on patients and society. Recent studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 111 publications
(118 reference statements)
0
23
0
Order By: Relevance
“…The role of miRs as regulatory molecules is observed in all phases of the wound healing process including the inflammation phase and proliferation phase involving angiogenesis, re-epithelialization, and granulation tissue formation to accelerate wound healing process [ 309 , 310 ]. A list of miRs and their role in different phases of wound healing is listed in Table 5 .…”
Section: Innovative Strategies For Wound Healingmentioning
confidence: 99%
“…The role of miRs as regulatory molecules is observed in all phases of the wound healing process including the inflammation phase and proliferation phase involving angiogenesis, re-epithelialization, and granulation tissue formation to accelerate wound healing process [ 309 , 310 ]. A list of miRs and their role in different phases of wound healing is listed in Table 5 .…”
Section: Innovative Strategies For Wound Healingmentioning
confidence: 99%
“…Small, non-coding RNAs, namely miRNAs (18–24 nucleotides), play a vital role in regulating apoptosis by intrinsic and extrinsic pathways [ 25 ]. These molecules act post-translationally, targeting pro-and anti-apoptotic genes [ 25 , 26 , 27 ]. It was found that an overexpressed miR-761 might alleviate chronic inflammation and induce the remodelling of nasal mucosa in CRS mice.…”
Section: Introductionmentioning
confidence: 99%
“…As the largest organ of the human body, the skin requires a large amount of highly regulated miRNAs for its development and morphogenesis. miRNAs are involved in skin immunity, cell proliferation, aging, pigmentation, wound healing, and cutaneous microbiomes [ 18 , 19 ]. miRNAs also play a role in skin cancers, inflammatory skin diseases, and autoimmune skin disorders.…”
Section: Introductionmentioning
confidence: 99%